2014
DOI: 10.1038/cr.2014.120
|View full text |Cite
|
Sign up to set email alerts
|

Liver Med23 ablation improves glucose and lipid metabolism through modulating FOXO1 activity

Abstract: Mediator complex is a molecular hub integrating signaling, transcription factors, and RNA polymerase II (RNAPII) machinery. Mediator MED23 is involved in adipogenesis and smooth muscle cell differentiation, suggesting its role in energy homeostasis. Here, through the generation and analysis of a liver-specific Med23-knockout mouse, we found that liver Med23 deletion improved glucose and lipid metabolism, as well as insulin responsiveness, and prevented diet-induced obesity. Remarkably, acute hepatic Med23 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 70 publications
1
50
0
Order By: Relevance
“…Yet another study demonstrated that MED15 is required for SREBP-1 activation of lipogenic target genes in nematodes (Yang et al, 2006). MED1, MED14, and MED23 are required for adipocyte development, and are ultimately involved in lipid metabolism as well (Chu et al, 2014; Zhang et al, 2013). Interestingly, the nuclear corepressor RIP140 interacts with CDK8 to regulate gene expression during fibroblast-adipocyte differentiation (Nautiyal et al, 2013).…”
Section: Metabolic Functions Of Mediator Components In Musclementioning
confidence: 99%
“…Yet another study demonstrated that MED15 is required for SREBP-1 activation of lipogenic target genes in nematodes (Yang et al, 2006). MED1, MED14, and MED23 are required for adipocyte development, and are ultimately involved in lipid metabolism as well (Chu et al, 2014; Zhang et al, 2013). Interestingly, the nuclear corepressor RIP140 interacts with CDK8 to regulate gene expression during fibroblast-adipocyte differentiation (Nautiyal et al, 2013).…”
Section: Metabolic Functions Of Mediator Components In Musclementioning
confidence: 99%
“…Numerous members of the NR family are sensors of metabolic status that respond to dietary signals and metabolites, and are responsible for metabolic adaptation at the cell, organ, and whole organismal level (Fig. 3) (Ito and Roeder 2001; Ge et al 2002, 2008; Huss 2004; Smith and Muscat 2005; Yang et al 2006; Wang et al 2009; Chen et al 2010; Grontved et al 2010; Krebs et al 2011; Rana et al 2011; Grueter et al 2012; Zhao et al 2012; Baskin et al 2014; Chu et al 2014; Jia et al 2014, 2016; Lee et al 2014; Amoasii et al 2016). Mediator complex subunits have been shown to interact strongly with numerous NRs in a ligand-dependent manner, and to interact with transcription factors to regulate a variety of metabolic processes.…”
Section: The Mediator Complexmentioning
confidence: 99%
“…For example, MED1, a core Mediator subunit, binds to nuclear receptors, and its deletion in skeletal muscle enhances metabolism (Chen et al 2010;Jia et al 2014). Additional components of the Mediator complex are involved in fatty acid, cholesterol, and lipid homeostasis (Yang et al 2006;Zhao et al 2012;Tsai et al 2013;Chu et al 2014). We reported that cardiac overexpression of MED13 increases energy consumption and confers a lean phenotype in mice (Grueter et al 2012;Baskin et al 2014).…”
mentioning
confidence: 95%